Deception counterdeception and counterintelligence - Clark, Robert M.; Mitchell, William L. q (William Leslie) (Sage / CQ Press, 2019)
"Bridging the divide between theory and practice, William L. Mitchell and Robert M. Clark's Deception: Counterdeception and Counterintelligence provides a thorough overview of the principles of deception and its uses in intelligence operations. This masterful guide focuses on practical training in deception for both both operational planners and intelligence analysts using a case-based approach. By reading and working through the exercises in this text, operations planners will learn how to build and conduct a deception campaign; and intelligence analysts will develop the ability to recognize deception and support deception campaigns."--Provided by publisher